2x-5y=-1;6x-5y=27
Solution :
{x,y} = {7,3}
System of Linear Equations entered :
[1] 2x - 5y = -1
[2] 6x - 5y = 27
Graphic Representation of the Equations :
-5y + 2x = -1 -5y + 6x = 27
Solve by Substitution :
// Solve equation [2] for the variable x
[2] 6x = 5y + 27
[2] x = 5y/6 + 9/2
// Plug this in for variable x in equation [1]
[1] 2•(5y/6+9/2) - 5y = -1
[1] - 10y/3 = -10
[1] - 10y = -30
// Solve equation [1] for the variable y
[1] 10y = 30
[1] y = 3
// By now we know this much :
x = 5y/6+9/2
y = 3
// Use the y value to solve for x
x = (5/6)(3)+9/2 = 7
Solution :
{x,y} = {7,3}
Hope I helped! :)